Neonatal intrahepatic cholestasis caused by citrin deficiency: clinical features, genetic characteristics, and treatment outcomes - Yigui Zou; Yu Dai; Liang Liu; Qinghua Yang; Wenwen Li; Yilin Dong; Sicong Li; Yongwei Cheng; Dongling Dai (BMC Gastroenterology)
Abstract Background Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) is an autosomal recessive disorder with heterogeneous clinical manifestations. This study aimed to characterize the clinical, biochemical, and genetic spectrum of NICCD and evaluate treatment outcomes. Methods This retrospective cohort study analyzed molecularly confirmed cases of NICCD admitted to Shenzhen Children’s Hospital between March 2019 and April 2023. Comprehensive clinical data were extracted from electronic records and analyzed using descriptive statistical methods. Results The cohort (n = 15) demonstrated universal jaundice (100%) and hyperammonemia (93.3%), with the predominant c.851_854del variant (52%) associated with earliest onset (median 3 days) and most severe cholestatic features (100% jaundice, 60% hepatomegaly). Key metabolic abnormalities included universal citrulline elevation (100%) and frequent methionine increase (93.3%), while threonine/tyrosine disturbances showed genotype-dependent patterns. All patients achieved complete symptom resolution (median 32 days) and significant growth improvement with lactose-free MCT formula and ursodeoxycholic acid therapy, though rare variants (compound heterozygous c.1399 C > T/c.1638_1660dup) exhibited markedly prolonged recovery (88 days vs. cohort median 32 days). Conclusions This study delineates the clinical-genetic spectrum of NICCD and confirms the efficacy of MCT-based therapy. Genotype-phenotype correlations suggest variant-specific disease severity, warranting multicenter validation for rare mutations.